(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2026)
This study aims to determine: (1) the effect of discounts on customer intention for word of mouth, (2) the effect of service quality on customer intention for word of mouth, (3) the effect of customer satisfaction on customer intention for word of mouth, (4) customer satisfaction mediates the effect of discounts on customer intention for word of mouth, (5) customer satisfaction mediates the effect of discounts on customer intention for word of mouth. The sample used was 100 respondents using purposive sampling technique. Data analysis using SEM PLS with SmartPLS 3 software. The results show that: (1) discounts have a significant effect on customer intention for word of mouth, (2) service quality has a significant effect on customer intention for word of mouth, (3) customer satisfaction has a significant effect on customer intention for word of mouth, (4) customer satisfaction partially mediates the effect of discounts on customer intention for word of mouth, and (5) customer satisfaction partially mediates the effect of service quality on customer intention for word of mouth.